(untitled) (Annals of Medical Research, 2023)
Aim: One of the technological advances in wound healing is negative pressure wound therapy (NPWT). NPWT is frequently used in acute and chronic wound care. However, few studies in the literature have investigated the effects of NPWT on the graft in patients with diabetic foot ulcers. In this study, we aimed to assess the effects of applying negative pressure wound closure on grafts and its influence on. The healing time indiabetic foot ulcers and thus contribute to the literature by sharing our experience. Materials and Methods: We retrospectively evaluated patients who had received treatment for diabetic foot ulcers in the chronic wound care unit of our hospital between February 2018 and October 2021 and underwent split-thickness skin grafting. The patients were categorized into two groups: those who did and did not receive NPWT to provide support for the graft. The patients were compared in terms of wound healing rates and healing times. Results: The study included 34 men (56.7%) and 26 women (43.3%) (n = 60). The mean age of the patients was 62.07 ± 11.5 years. Supportive NPWT was performed on the graft in 19 (31.7%) patients, whereas 41 (68.3%) patients were treated with grafting and conventional therapy. The treatment duration was shorter in the NPWT group (29.63 ± 19.6 days) than in the non-NPWT group (34.05 ± 17.5 days); however, this difference was not significant (p > 0.05). A significant weak positive correlation (r = 0.28) was observed between the Wagner stage and treatment duration. Conclusion: The treatment of diabetic foot ulcers is affected by several factors, including the presence of infection, vascularization status, wound size, and glycemic control. In this study, we examined a general patient population with diabetic foot ulcers and identified no significant difference in terms of treatment times and healing rates between NPWT and conventional methods as graft-supporting measures. Prospective studies investigating patient populations comprising subgroups may yield varying results, which emphasizes the need for further research in this direction.